Theoretical calculations on the structural, electronic, and optical properties of bulk silver nitrides. Issue 12 (28th August 2015) - Suleiman, Mohammed S. H.; Joubert, Daniel P.
Abstract: The extreme endothermic nature of silver nitride has been hampering its experimental characterization and there is incomplete detailed knowledge of the structural and physical properties of this material. Stimulated by this lack, we present a first‐principles DFT and GW investigation of structural, electronic, and optical properties of bulk crystalline silver nitrides. In this study, 20 structures for Ag 3 N, AgN, and AgN 2 were investigated. The equilibrium cohesive and formation energies revealed that the AgN 2 series contains the most energetically stable phases. However, all the formation energies confirmed that silver nitrides are thermodynamically unstable. New possible structural phase transitions were discovered from the enthalpy–pressure equation of states diagrams. We predict that the most stable phases of AgN and AgN 2 are metallic, while those of Ag 3 N are semiconductors. In agreement with a previous study, it is found that as the nitrogen to silver ratio decreases, the total DOS at Fermi energy decreases until a gap opens. The calculated lattice parameter of Ag 3 N(D09)—the most stable modification in the considered Ag 3 N phases—is close to the experimentally reported one, yet the calculated absorption spectrum does not explain the observed black color of the synthesized Ag 3 N.